A family of long reiterated DNA sequences, one copy of which is next to the human beta globin gene. - Adams, J W (1980)
An unusually long repeated DNA sequence was identified in cloned DNA, three kb 3' to the human beta-globin gene. Other members of this repeated sequence family were isolated from a human genomic DNA library and characterized by Southern blotting techniques, electron microscopy, and solution hybridization. The copy located next to the beta-globin gene was found to be 6.4 +/- 0.2 kb long and continuous over that length. This repeated sequence family comprises about 1% of the human genome and contains 3000-4800 copies of moderate sequence divergence which are interspersed with other less-highly repeated DNA. The 6.4 kb repeated unit does not appear to be composed of any smaller tandemly repeated subunits, nor is it expressed at a high level in bone marrow cell RNA.